Improving Tolitoli Language Skills Through Visual Learning Media in Elementary School - Marto, Hasia; Wukungsenggo, Yolpi; Sari, Nur Inda; Yago, Ribka; Jenista, Anjela (research, training and philanthropy institution Natural Aceh, 2025)
The crisis challenges experienced by the Tolitoli language cannot be separated from the cultural and linguistic acculturation process in the Tolitoli Regency. This study assesses how effective visual learning media improves Tolitoli's language skills in IPAS lessons at SDN 1 Nalu. The method used is qualitative with a descriptive approach. Involves observation, interviews, and listening guides with participants consisting of class IV student guardians and class IV students. This research was conducted at SD Negeri 1 Nalu. The results showed that the use of visual media based on local wisdom of Tolitoli local language in IPAS lessons had a positive impact, such as increasing appreciation for local culture, effective use in learning, and student's understanding of the material increased because learning was presented concretely so that students did not just fantasize in the classroom but could see a picture of the material being explained. Therefore, to support the preservation of Tolitoli language culture among students, using visual media is very effective so that it can be applied to other lessons.